Watch
Announcements
#1
C(s) + O2(g) → CO2(g) DH° = –396kJ mol–1
Pb(s) + ½O2(g) → PbO(s) DH° = –210kJ mol–1
PbO(s) + CO(g) → Pb(s) + CO2(g) DH° = –74kJ mol–1

What is the value of DH°, in kJ mol–1, for the
following reaction?

C(s) + ½O2(g) → CO(g)

A –260
B –112
C +112
D +260

I have tried for really long and the answer that i get isn't even an option, hahaha. Could you please explain also??? 0
4 years ago
#2
(Original post by flyingpanda786)
C(s) + O2(g) → CO2(g) DH° = –396kJ mol–1
Pb(s) + ½O2(g) → PbO(s) DH° = –210kJ mol–1
PbO(s) + CO(g) → Pb(s) + CO2(g) DH° = –74kJ mol–1

What is the value of DH°, in kJ mol–1, for the
following reaction?

C(s) + ½O2(g) → CO(g)

A –260
B –112
C +112
D +260

I have tried for really long and the answer that i get isn't even an option, hahaha. Could you please explain also??? How about replacing that reaction with the reaction  0
#3
(Original post by NDVA)
How about replacing that reaction with the reaction  hmmm still not sure i keep getting -532kJ mol-1
0
4 years ago
#4
(Original post by flyingpanda786)
hmmm still not sure i keep getting -532kJ mol-1
I think you just made a mistake somewhere about the signs Let the required be . has But has Hence so , which is option B 1
4 years ago
#5
(Original post by flyingpanda786)

equation 1: C(s) + O2(g) → CO2(g) DH° = –396kJ mol–1
equation 2: Pb(s) + ½O2(g) → PbO(s) DH° = –210kJ mol–1
equation 3: PbO(s) + CO(g) → Pb(s) + CO2(g) DH° = –74kJ mol–1

What is the value of DH°, in kJ mol–1, for the
following reaction?

C(s) + ½O2(g) → CO(g)

A –260
B –112
C +112
D +260

I have tried for really long and the answer that i get isn't even an option, hahaha. Could you please explain also??? Because of Hess' law any mathematical operation may be carried out on an equation provided you do the same to the energy change.

The idea here is that you construct the required equation by manipulation of the given equations. My advice is to do so one step at a time.

You need C(s) and this appears in equation 1

C(s) + O2(g) → CO2(g)

But you don't need CO2(g) so subtract equation 3 from 1
C(s) + O2(g) → CO2(g)
PbO(s) + CO(g) → Pb(s) + CO2(g)
---------------------------------------------- subtract
C(s) + O2(g) - PbO(s) - CO(g) → CO2(g) - Pb(s) - CO2(g)

cancelling down

C(s) + O2(g) - PbO(s) - CO(g) → -Pb(s)

rearranging to make all terms positive gives

C(s) + O2(g) + Pb(s) → PbO(s) + CO(g)

Now you want rid of the PbO(s) term so subtract equation 2

C(s) + O2(g) + Pb(s) → PbO(s) + CO(g)
Pb(s) + ½O2(g) → PbO(s)
------------------------------------- subtract
C(s) + ½O2(g) → CO(g)

Which is your target equation. Simply follow each step using the energy to get the answer ...
0
4 years ago
#6
If it's tricky then draw a piccy
0
#7
(Original post by TeachChemistry)
If it's tricky then draw a piccy
wow!! that must have taken you a while haha. That was really nice of you thank you for your help and time budd, really appreciate it!!! 0
X

new posts Back
to top
Latest
My Feed

### Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

### See more of what you like onThe Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

### Poll

Join the discussion

Yes (64)
61.54%
No (40)
38.46%